Validation of the Korean-Version of the Clinical Assessment Interview for Negative Symptoms of Schizophrenia (CAINS) - Jung, Sung Il (J Korean Med Sci, 2016)
The Clinical Assessment Interview for Negative Symptoms (CAINS) was developed to overcome the limitations of existing instruments and reflect the current view of negative symptoms. The aim of the present study was to evaluate the reliability and validity of the Korean version of the Clinical Assessment Interview for Negative Symptoms (K-CAINS). Inpatients (n = 49) and outpatients (n = 70) with schizophrenia were recruited from three institutions. The confirmative factor analysis, test-retest reliability, inter-rater reliability, convergent validity, and discriminant validity were assessed. The study group consisted of 71 males (59.7%) and 48 females (40.3%). Their mean age was 42.15 years (SD = 12.2). The K-CAINS was confirmed to be divided into two subscales of 9 items related to "motivation/pleasure" and 4 items related to "expression" in concordance with the original version of the CAINS. The results showed that the K-CAINS had a good inter-rater reliability (ICC = 0.84-0.94), test-retest reliability (r = 0.90, P < 0.001). Convergent validity was proven by demonstrating a significant correlation with the Positive and Negative Syndrome Scale (PANSS) negative subscale, and the Scale for the Assessment of Negative Symptoms (SANS). Discriminant validity was proven by the lack of a significant correlation with the PANSS positive subscale, the Korean version of the Beck depression inventory (BDI), the Korean version of the Calgary depression scale for schizophrenia (K-CDSS), and the Modified Simpson Angus scale (MSAS). The K-CAINS could be a reliable and valid tool to assess the negative symptoms of Korean schizophrenia patients.